NGHIÊN CỨU LÍ THUYẾT CƠ CHẾ PHẢN ỨNG GIỮA C2H VÀ C2H5CN - Trị, Trần Quốc; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
The reaction mechanism of the Ethynyl radical and propanenitrile has been studied by the Density Functional Theory (DFT) using the BHandHLYP functional in conjunction with the 6-311++G(d,p) and 6-311++G(3df,2p) basis sets. The potential energy surface (PES) for the C2H+C2H5CN system was also established. Calculated results indicate that products of this reaction can be (HCCH + CH2CH2CN), (HCCCH3+H2CCN), (HCCH+CH3CHCN), (H2CC +CH2CH2CN), (H2CC + CH3CHCN), (HCCNCCH2CH3 + CN), (HCCNCCH2 + CH3), (HCCNC + CH3CH2) and (HCCCN + CH3CH2). However, the formation of (HCCH + CH3CHCN), (HCCH + CH2CH2CN) and (HCCCN + CH3CH2) is the most favorable. This study is a contribution to the understanding of the reaction mechanisms of the ethynyl radical with many small radicals and molecules in the atmosphere and combustion chemistry.